Exploring the Role of Digital Tools in Ethical Managerial Decision-Making - Miguel Álvarez; Leila Hassan (Journal of Management and Informatics, 2025)
The rapid integration of digital technologies into managerial work reorganized ethical decision-making in organizations. Technology holds the promise of efficiency and transparency but leaves the impact of technology on moral thought and managerial accountability unclear. This research strives to analyze how digital technologies inform, enable, or complicate ethical managerial decision-making. Utilizing a qualitative exploratory research methodology, the research weaves evidence from an in-depth literature review and semi-structured interviews on Ethical Decision-Making Theory and Socio-Technical Systems Theory. Thematic coding suggests that online resources can enhance ethical consistency and moral awareness if used reflectively but reduce moral sensitivity based on reliance on algorithmic rationality. The findings suggest dynamic interplay between human judgment and computer mediation and underscore the merits of socio-technical integration under balance. A conceptual model for co-evolution modeling of digital intelligence and moral cognition in managerial contexts is proposed. Ethical decision-making in the digital era, this study argues, is less a question of algorithmic transparency and more a question of applying responsible human judgment in technologically mediated environments. The research makes a theoretical contribution by merging ethical thinking with socio-technical models of management and provides organisational practical advice on how to integrate moral thinking within digital environments of decision-making.